Catalytic Asymmetric Iodocyclization of N‐Tosyl Alkenamides using Aminoiminophenoxy Copper Carboxylate: A Concise Synthesis of Chiral 8‐Oxa‐6‐Azabicyclo[3.2.1]octanes. (14th September 2015) - Arai, Takayoshi; Watanabe, Ohji; Yabe, Shinnosuke; Yamanaka, Masahiro
Abstract A newly developed aminoiminophenoxy copper carboxylate (L7‐Cu‐OAc)‐catalyzed asymmetric iodocyclization of N‐Tosyl alkenamides gave O‐cyclized products in good yields with high enantioselectivity. From the O‐cyclized products, a skeletal transformation was succeeded in the synthesis of biologically important chiral 8‐oxa‐6‐azabicyclo[3.2.1]octanes. DFT calculations suggested that the acetoxy anion of the [L7‐Cu‐OAc] acts as a base to generate the anion of N‐Tosyl alkenamide substrates. The exchanged acetic acid reconstructs a new hydrogen‐bonding network between the catalyst and the substrates to accomplish the highly efficient asymmetric O‐iodocyclization of N‐Tosyl alkenamides.